Territorial Structure of Agriculture Development in Uzbekistan in Terms of Economical Geography - KOMILOVA, NilufarKh.; HAYDAROVA, Suraya A.; XALMIRZAEV, Ahmadjan A.; KURBANOV, Shukhrat B.; RAJABOV, Furkat T. (Journal of Advanced Research in Law and Economics; Vol 10 No 8 (2019): JARLE Volume X Issue 8(46) Winter 2019, 2019)
The article deals with the geographical study of agricultural development in Uzbekistan, the legal framework related to agricultural development in the country during independence, the emergence of permanent settlement based on irrigated agriculture, the importance of scientific development, and agricultural development. Uzbekistan since ancient times. Historical materials are analyzed. In recent years, analyzes have been undertaken to improve the territorial structure of agricultural sectors in the Jizzakh region. It focuses on the natural conditions, climatic resources of Jizzakh region, its ancient and mountainous areas, on rain-fed grain and horticultural areas, cotton growing areas, agro-climatic resources and its regional differences. Some features related to the agricultural location of the Jizzakh region include: wide opportunities for agricultural productivity in mountainous and foothill areas; Farming in steppe regions is largely due to the size of the fields and the need to deal with natural factors that limit productivity. The study used statistical, questionnaires, geographical comparisons, cartographic, regional analysis, extrapolation.